Design and prototype of a six-legged walking insect robot - Soyguder, Servet; Alli, Hasan (Emerald Group Publishing Ltd, 2007)
Purpose - This paper seeks to develop a novel legged robot. Design/methodology/approach - First, the paper models the legged robot using 3D computer model by intelligent inspiration of biological principles. Then, based on this model, it develops the prototype of the legged robot. Findings - A novel motion mechanism is used and only two actuators are used for driving the system. Originality/value - The modelled legged robot is original in terms of the developed motion mechanism.
Keywords: prototypes; motion; actuators; robotics